Tribhuvan University Pioneering Higher Education in the History of Nepal - Karna, Manoj Kumar (Historical Journal, 2024)
As per the requirement of changes in higher education to meet the global challenges in the different time beings, Nepal has been witnessing the formal education planning since 1955 and especially the high level education commission since 1983 with various updates in every step. Historically, Tribhuvan University (TU) is the only central and the eldest university of Nepal which carries about eighty percent weight of higher education and its activities are demonstratively a sample for other universities of Nepal. Currently, Nepal has seventeen universities and still there are many in the pipeline. Despite having many sources of higher education in Nepal, the brain drain is a major problem here. This research article consults different book, websites, report and the relevant recent media sources to make a true sense of the qualitative research. A historical brief study of higher education of Nepal, the planner and the stake-holders will get insights for quality education so that the universities like TU will retain its glorious image again.